Two new species of Macroplea Samouelle (Coleoptera: Chrysomelidae: Donaciinae) from China, with a key to all known species - Lou, Qiaozhe; Yu, Peiyu; Liang, Hongbin (Zootaxa, 2011)
Two new species of the aquatic leaf beetle genus Macroplea Samouelle namely M. ranina Lou & Yu, sp. nov. and M. huaxiensis Lou & Liang, sp. nov. are described from China. Macroplea appendiculata (Panzer, 1794) is recorded for the first time from China and a key to all known species of Macroplea is provided.